The European Values Study 2017: On the Way to the Future Using Mixed-Modes. (24th November 2020) - Luijkx, Ruud; Jónsdóttir, Guðbjörg Andrea; Gummer, Tobias; Ernst Stähli, Michèle; Frederiksen, Morten; Ketola, Kimmo; Reeskens, Tim; Brislinger, Evelyn; Christmann, Pablo; Gunnarsson, Stefán Þór; Hjaltason, Árni Bragi; Joye, Dominique; et al.
Abstract: The European Values Study (EVS) was first conducted in 1981 and then repeated in 1990, 1999, 2008, and 2017, with the aim of providing researchers with data to investigate whether European individual and social values are changing and to what degree. The EVS is traditionally carried out as a probability-based face-to-face survey that takes around 1 hour to complete. In recent years, large-scale population surveys such as the EVS have been challenged by decreasing response rates and increasing survey costs. In the light of these challenges, six countries that participated in the last wave of the EVS tested the application of self-administered mixed-modes (Denmark, Finland, Germany, Iceland, the Netherlands, and Switzerland). With the present data brief, we will introduce researchers to the latest wave of the EVS, the implemented mode experiments, and the EVS data releases. In our view, it is pivotal for data use in substantive research to make the reasoning behind design changes and country-specific implementations transparent as well as to highlight new research opportunities.